A silicon carbide ceramic based on rare earth metal elements and a preparation method thereof
Patent Information
- Application Number
- CN202610936820.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-26
- Publication Date
- 2026-10-30
AI Technical Summary
该方案虽在一定程度上避免了液相过早流失,但存在明显局限:一方面,熔盐法工艺复杂,合成步骤繁琐,增加了制备周期和成本;另一方面,熔盐介质及后续处理过程易引入氧杂质,残留的氧会固溶于SiC晶格或偏聚于晶界,形成声子散射中心,严重制约了材料热导率的进一步提升
1.本发明采用稀土金属作为烧结助剂,在第一阶段烧结阶段,形成液相,同时消耗体系中的氧杂质,从源头上降低了陶瓷的表面氧与内部晶格氧含量,避免了传统稀土氧化物助剂本征含氧而额外引入氧杂质的缺陷;在第二阶段烧结阶段,在低氧液相环境能够有效促进碳化硅陶瓷的致密化进程,通过“溶解-沉淀”机制优化晶界结构,减少声子散射源。同时,稀土金属的持续脱氧作用进一步降低材料的晶格氧与表面氧含量,使最终得到的碳化硅陶瓷拥有均匀的物相分布与低缺陷微观结构,从而显著提升材料的热导率。
Smart Images

Figure CN123003294A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ceramic materials technology, and relates to a silicon carbide ceramic based on rare earth metal elements and its preparation method. Background Technology
[0002] Silicon carbide (SiC) ceramics possess excellent properties such as high thermal conductivity, high temperature resistance, corrosion resistance, and high hardness, making them promising for applications in extreme environments such as electronic packaging, heat dissipation for high-power devices, high-temperature heat exchangers, and aerospace. However, the thermal conductivity of currently available SiC materials remains limited, failing to fully meet the demands of certain high-end applications. This limitation primarily stems from microstructural defects formed during the sintering process of SiC ceramics. The theoretical thermal conductivity of single-crystal SiC is 490 W / mK; however, during the sintering process, intragranular defects such as solid solution impurities, vacancies, and dislocations, as well as grain boundary defects such as grain boundaries, residual grain boundary phases, and pores, are generated within the SiC grains. These defects reduce the thermal conductivity of polycrystalline SiC ceramics.
[0003] To overcome these bottlenecks, researchers have tried various additives and process solutions, but all have limitations. Traditional rare earth oxides, due to their inherent oxygen content, introduce additional oxygen impurities during sintering, failing to minimize the lattice oxygen content of the ceramic. While rare earth carbides have strong deoxidizing capabilities, their extremely high chemical reactivity makes them highly susceptible to moisture absorption, hydrolysis, and deterioration at room temperature, resulting in extremely poor stability during powder storage and batching, and making precise batching difficult to control. Rare earth hydrides decompose and release hydrogen gas during sintering, easily generating pores and causing a decrease in ceramic density. Rare earth metals also exhibit high chemical reactivity, readily oxidizing in air, which not only reduces their reactivity but also introduces additional oxygen impurities into the system, affecting deoxidation. Furthermore, the high reactivity of rare earth metals with silicon carbide leads to excessively rapid reaction rates during direct mixing and one-step sintering, making it difficult to coordinate the liquid phase formation and densification processes. This can easily result in premature liquid phase loss, abnormal grain growth, and localized overheating, hindering stable densification sintering. To control the reaction rate and prevent premature liquid phase loss, some researchers have proposed using a molten salt method to pre-synthesize ternary rare earth carbides, which are then used as sintering aids. While this approach avoids premature liquid phase loss to some extent, it has significant limitations: firstly, the molten salt method is complex, with cumbersome synthesis steps, increasing the preparation cycle and cost; secondly, the molten salt medium and subsequent processing easily introduce oxygen impurities, and residual oxygen can dissolve in the SiC lattice or agglomerate at grain boundaries, forming phonon scattering centers, which severely restricts further improvement in the material's thermal conductivity.
[0004] Therefore, in view of the technical bottlenecks of the existing rare earth additive system, it is urgent to develop a new silicon carbide ceramic processing technology that uses rare earth metal elements as additives, which can give full play to their strong deoxidation advantages and avoid the introduction of additional impurities from the source. Summary of the Invention
[0005] The purpose of this invention is to address the aforementioned problems in the existing technology by proposing a method for preparing silicon carbide ceramics based on rare earth metals, using rare earth metals as sintering aids to obtain silicon carbide ceramic materials with high thermal conductivity.
[0006] The first objective of this invention is achieved through the following technical solution: A method for preparing silicon carbide ceramics based on rare earth metals includes the following steps: (1) Silicon carbide powder with a molar ratio of 88:12 to 92:8 is mixed with rare earth metal element powder to obtain mixed powder; wherein, the rare earth metal element RE is selected from at least one of Yb, Sm, Gd, Y, Er and Dy; (2) Under an inert atmosphere, the mixed powder is placed in a spark plasma sintering furnace, a pressure of 1~100MPa is applied, and the temperature is raised to 1100~1540℃ at a heating rate of 20~60℃ / min for the first stage of sintering and held for 20~90min. Then, the temperature is continuously raised to 2010~2100℃ at a heating rate of 10~40℃ / min for the second stage of sintering and held for 20~90min to obtain silicon carbide ceramic.
[0007] Preferably, in step (1), the rare earth metal element RE is selected from at least one of Sm, Y, and Er.
[0008] Further optimization yielded rare earth metal element RE of Y.
[0009] Preferably, in step (1), the molar ratio of silicon carbide powder to rare earth metal powder is 90:10.
[0010] Preferably, in step (1), the average particle size of the silicon carbide powder is 0.1~10μm.
[0011] Preferably, in step (1), the average particle size of the rare earth metal elemental powder is 40~300μm.
[0012] Further optimization yields rare earth metal elemental powders with an average particle size of 60~90μm.
[0013] Preferably, in step (1), the mixture is selected from at least one of crushing, dry ball milling, wet ball milling, grinding, drying, and sieving.
[0014] Further optimization involves mixing in sequence, including wet ball milling, drying, and sieving.
[0015] Preferably, in step (2), the inert atmosphere is selected from at least one of nitrogen and argon.
[0016] Preferably, in step (2), the pressure of the first stage of sintering is 10~40MPa.
[0017] Preferably, in step (2), the heating rate of the first stage sintering is 45~55℃ / min, the sintering temperature is 1410~1490℃, and the sintering time is 30~80min.
[0018] Preferably, in step (2), the heating rate of the first stage sintering is 50℃ / min, the sintering temperature is 1450℃, and the sintering time is 60min.
[0019] Preferably, in step (2), a liquid phase is formed after the first stage of sintering.
[0020] Preferably, in step (2), the pressure of the second stage sintering is 10~40MPa.
[0021] Preferably, in step (2), the heating rate of the second stage sintering is 22~30℃ / min, the sintering temperature is 2020~2070℃, and the sintering time is 30~80min.
[0022] Preferably, in step (2), the heating rate of the second stage sintering is 25℃ / min, the sintering temperature is 2050℃, and the sintering time is 60min.
[0023] If the sample is cooled after the first-stage sintering and then heated again for the second-stage sintering, severe abnormal grain growth may occur, potentially leading to invisible microcracks within the sample. These cracks cannot fully heal during the second high-temperature sintering and instead become phonon scattering centers, further reducing thermal conductivity. If the temperature is directly increased to the second-stage sintering temperature without holding at the first-stage temperature, the density and thermal conductivity of the silicon carbide ceramic will be affected. If the holding time in the second-stage sintering stage is too short, the reaction will be incomplete, also affecting the density and thermal conductivity of the silicon carbide ceramic.
[0024] Preferably, in step (2), the heating rate of the second stage sintering is less than the heating rate of the first stage sintering.
[0025] The second objective of this invention is achieved through the following technical solution: A silicon carbide ceramic is prepared by the above-described method.
[0026] Preferably, the silicon carbide ceramic has a bulk density of 3.1~3.3 g / cm³. 3 .
[0027] Preferably, the open porosity of the silicon carbide ceramic is ≤0.91%.
[0028] Further preferably, the open porosity of the silicon carbide ceramic is <0.6%.
[0029] Preferably, the lattice oxygen content of the silicon carbide ceramic is ≤0.3wt%.
[0030] Further preferably, the lattice oxygen content of the silicon carbide ceramic is ≤0.06wt%.
[0031] More preferably, the lattice oxygen content of the silicon carbide ceramic is <0.05wt%.
[0032] Preferably, the thermal conductivity of the silicon carbide ceramic is >222 W / mK.
[0033] Further preferably, the thermal conductivity of the silicon carbide ceramic is >231 W / mK.
[0034] More preferably, the thermal conductivity of the silicon carbide ceramic is >256W / mK.
[0035] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention uses rare earth metals as sintering aids. In the first sintering stage, a liquid phase is formed, simultaneously consuming oxygen impurities in the system. This reduces the surface oxygen and internal lattice oxygen content of the ceramic from the source, avoiding the defect of traditional rare earth oxide aids that inherently contain oxygen and introduce additional oxygen impurities. In the second sintering stage, the low-oxygen liquid phase environment effectively promotes the densification process of silicon carbide ceramics. The grain boundary structure is optimized through a "dissolution-precipitation" mechanism, reducing phonon scattering sources. Simultaneously, the continuous deoxidation effect of rare earth metals further reduces the lattice oxygen and surface oxygen content of the material, resulting in a silicon carbide ceramic with a uniform phase distribution and a low-defect microstructure, thereby significantly improving the thermal conductivity of the material.
[0036] 2. This invention employs spark plasma sintering, which effectively suppresses the slow oxidation and volatilization of rare earth metals. It avoids problems such as liquid phase loss, abnormal grain growth, and local overheating caused by slow heating rates in traditional hot pressing or pressureless sintering, ensuring the stable progress of deoxidation and densification processes and obtaining a uniform and dense microstructure.
[0037] 3. The silicon carbide ceramics prepared by this invention have high density and high thermal conductivity, and have important application value in the fields of semiconductor heat dissipation components, high-temperature heat exchangers and high-performance structural ceramics. Attached Figure Description
[0038] Figure 1 This is the XRD pattern of the sintering intermediate in Embodiment 2 of the present invention.
[0039] Figure 2 This is a SEM image of the silicon carbide ceramic in Example 2 of the present invention.
[0040] Figure 3 This is the XRD pattern of the silicon carbide ceramic in Example 2 of the present invention.
[0041] Figure 4 This is the XRD pattern of the sintering intermediate in Example 5 of the present invention.
[0042] Figure 5 This is the XRD pattern of the silicon carbide ceramic in Example 5 of the present invention.
[0043] Figure 6 This is the XRD pattern of the sintering intermediate in Comparative Example 5 of the present invention.
[0044] Figure 7 This is a SEM image of the silicon carbide ceramic in Comparative Example 5 of the present invention.
[0045] Figure 8 The image shows the XRD pattern of the silicon carbide ceramic in Comparative Example 5 of this invention. Detailed Implementation
[0046] The technical solution of the present invention will be further described and illustrated below through specific embodiments. It should be understood that the specific embodiments described herein are only for the purpose of helping to understand the present invention and are not intended to limit the present invention.
[0047] Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used in the art, and the methods used in the embodiments are all conventional methods in the art.
[0048] In this invention, the raw materials include: Silicon carbide powder (β-SiC), with a purity greater than 99.5% and an average particle size of 0.6 μm, was purchased from Qinhuangdao Yinuo New Material Technology Co., Ltd. Rare earth metal elemental powders (Yb, Sm, Gd, Y, Er, Dy), with a purity greater than 99.9% and an average particle size of 75 μm, were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0049] In this invention, the testing method includes: 1. Thermal conductivity test: The laser thermal conductivity method was used, and the test was conducted using a Netzsch LFA467 laser thermal conductivity meter from Germany.
[0050] 2. Test of open porosity and bulk density: Archimedes' method of drainage was used.
[0051] 3. Lattice oxygen content: After the sample is crushed, ground, acid-etched, centrifuged and ultrasonically treated, it is tested by an oxygen / nitrogen analyzer using the thermal gas extraction method.
[0052] 4. Phase analysis: Phase identification was performed using an X-ray diffractometer (XRD).
[0053] 5. Microscopic morphology observation: The microstructure of ceramics was observed using a scanning electron microscope (SEM).
[0054] Example 1 The preparation method of silicon carbide ceramics based on rare earth metals in this embodiment includes the following steps: (1) Weigh silicon carbide powder and rare earth metal element Y powder at a molar ratio of 88:12, place them in a ball mill jar, add anhydrous ethanol and zirconium oxide balls, and vacuum ball mill for 12 hours to obtain ceramic slurry; dry the ceramic slurry by rotary evaporation at 70°C and sieve to obtain mixed powder.
[0055] (2) The mixed powder is loaded into a graphite mold and placed in a spark plasma sintering furnace. In a flowing argon environment, a pressure of 30 MPa is applied, and the temperature is raised to 1450°C at a heating rate of 50°C / min. The temperature is held for 60 min to carry out the first stage of sintering and obtain a sintering intermediate. A pressure of 30 MPa is continuously applied, and the temperature is continuously raised to 2050°C at a heating rate of 25°C / min. The temperature is held for 60 min to carry out the second stage of sintering and then cooled with the furnace to obtain silicon carbide ceramic.
[0056] The silicon carbide ceramic of this embodiment was tested, and the results are shown in Table 1.
[0057] Example 2 The preparation method of silicon carbide ceramics based on rare earth metals in this embodiment includes the following steps: Compared with Example 1, the difference is that in step (1), the molar ratio of silicon carbide powder to rare earth metal element Y powder is 90:10.
[0058] The silicon carbide ceramic of this embodiment was tested, and the results are shown in Table 1.
[0059] Example 3 The preparation method of silicon carbide ceramics based on rare earth metals in this embodiment includes the following steps: Compared with Example 1, the difference is that in step (1), the molar ratio of silicon carbide powder to rare earth metal element Y powder is 92:8.
[0060] The silicon carbide ceramic of this embodiment was tested, and the results are shown in Table 1.
[0061] Example 4 The preparation method of silicon carbide ceramics based on rare earth metals in this embodiment includes the following steps: Compared with Example 2, the difference is that in step (1), the rare earth metal elemental powder is Yb.
[0062] The silicon carbide ceramic of this embodiment was tested, and the results are shown in Table 1.
[0063] Example 5 The preparation method of silicon carbide ceramics based on rare earth metals in this embodiment includes the following steps: Compared with Example 2, the difference is that in step (1), the rare earth metal elemental powder is Sm.
[0064] The silicon carbide ceramic of this embodiment was tested, and the results are shown in Table 1.
[0065] Example 6 The preparation method of silicon carbide ceramics based on rare earth metals in this embodiment includes the following steps: Compared with Example 2, the difference is that in step (1), the rare earth metal powder is Gd.
[0066] The silicon carbide ceramic of this embodiment was tested, and the results are shown in Table 1.
[0067] Example 7 The preparation method of silicon carbide ceramics based on rare earth metals in this embodiment includes the following steps: Compared with Example 2, the difference is that in step (1), the rare earth metal elemental powder is Er.
[0068] The silicon carbide ceramic of this embodiment was tested, and the results are shown in Table 1.
[0069] Example 8 The preparation method of silicon carbide ceramics based on rare earth metals in this embodiment includes the following steps: Compared with Example 2, the difference is that in step (1), the rare earth metal elemental powder is Dy.
[0070] The silicon carbide ceramic of this embodiment was tested, and the results are shown in Table 1.
[0071] Comparative Example 1 The preparation method of silicon carbide ceramics in this comparative example includes the following steps: Compared with Example 2, the difference is that in step (2), the mixed powder is loaded into a graphite mold, placed in a spark plasma sintering furnace, and subjected to a pressure of 30 MPa in a flowing argon atmosphere. The temperature is continuously increased to 2050°C at a heating rate of 25°C / min, and sintered for 120 min. The furnace is then cooled to obtain silicon carbide ceramic.
[0072] The silicon carbide ceramics of this comparative example were tested, and the results are shown in Table 1.
[0073] Comparative Example 2 The preparation method of silicon carbide ceramics in this comparative example includes the following steps: Compared with Example 2, the difference is that in step (2), the mixed powder is loaded into a graphite mold and placed in a spark plasma sintering furnace. In a flowing argon environment, a pressure of 30 MPa is applied and the temperature is raised to 1450°C at a heating rate of 50°C / min, held for 120 min, and then continuously raised to 2050°C at a heating rate of 25°C / min, held for 60 min for sintering. The furnace is then cooled to obtain silicon carbide ceramic.
[0074] The silicon carbide ceramics of this comparative example were tested, and the results are shown in Table 1.
[0075] Comparative Example 3 The preparation method of silicon carbide ceramics in this comparative example includes the following steps: Compared with Example 2, the difference is that in step (2), the heating rate of the second stage sintering is 5°C.
[0076] The silicon carbide ceramics of this comparative example were tested, and the results are shown in Table 1.
[0077] Comparative Example 4 The preparation method of silicon carbide ceramics in this comparative example includes the following steps: Compared with Example 2, the difference is that no pressure is applied during the second stage of sintering in step (2).
[0078] The silicon carbide ceramics of this comparative example were tested, and the results are shown in Table 1.
[0079] Comparative Example 5 The preparation method of silicon carbide ceramics in this comparative example includes the following steps: Compared with Example 2, the difference is that in step (1), the molar ratio of silicon carbide powder to rare earth metal element Y powder is 94:6.
[0080] The silicon carbide ceramics of this comparative example were tested, and the results are shown in Table 1.
[0081] Comparative Example 6 The preparation method of silicon carbide ceramics in this comparative example includes the following steps: Compared with Example 2, the difference is that in step (1), the molar ratio of silicon carbide powder to rare earth metal element Y powder is 80:20.
[0082] The silicon carbide ceramics of this comparative example were tested, and the results are shown in Table 1.
[0083] Comparative Example 7 The preparation method of silicon carbide ceramics in this comparative example includes the following steps: Compared with Example 2, the difference is that in step (2), the sintering temperature of the second stage sintering is 2000℃.
[0084] The silicon carbide ceramics of this comparative example were tested, and the results are shown in Table 1.
[0085] Comparative Example 8 The preparation method of silicon carbide ceramics in this comparative example includes the following steps: (1) Weigh silicon carbide powder and Y3Si2C2 with a molar ratio of 90:10, place them in a ball mill jar, add anhydrous ethanol and zirconium oxide balls, and vacuum ball mill for 12 hours to obtain ceramic slurry; dry the ceramic slurry by rotary evaporation at 70°C and sieve to obtain mixed powder.
[0086] (2) The mixed powder is loaded into a graphite mold and placed in a spark plasma sintering furnace. In a flowing argon atmosphere, a pressure of 30 MPa is applied, and the temperature is raised to 2050°C at a heating rate of 25°C / min. The temperature is held for 60 min for sintering, and the furnace is cooled to obtain silicon carbide ceramic.
[0087] The silicon carbide ceramics of this comparative example were tested, and the results are shown in Table 1.
[0088] Comparative Example 9 The preparation method of silicon carbide ceramics in this comparative example includes the following steps: Compared with Example 2, the difference is that in step (1), the sintering aid powder is YC2.
[0089] In this comparative example, YC2 itself has a high melting point and cannot form an effective liquid phase, thus making it impossible to achieve densification sintering of SiC ceramics.
[0090] Comparative Example 10 The preparation method of silicon carbide ceramics in this comparative example includes the following steps: Compared with Example 2, the difference is that in step (1), the sintering aid powder is YH2.
[0091] In this comparative example, YH2 has poor stability and is easily hydrolyzed, making it impossible to form an effective liquid phase during the reaction process, thus preventing the densification sintering of SiC ceramics.
[0092] Comparative Example 11 The preparation method of silicon carbide ceramics in this comparative example includes the following steps: The mixed powder from Example 2 was mixed with a molten salt of NaCl and KCl (molar ratio 1:1) and placed in an alumina crucible. The mixture was then transferred to a tube furnace and heated to 1100°C for 2 hours under a flowing argon atmosphere. After cooling to room temperature, the reaction product was repeatedly boiled in distilled water for washing and then dried at 70°C. Subsequently, it was placed in a graphite mold and sintered in a spark plasma sintering furnace. Under a flowing argon atmosphere, a pressure of 30 MPa was applied, and the temperature was continuously increased to 2050°C at a rate of 25°C / min, held for 60 minutes, and then cooled in the furnace to obtain silicon carbide ceramic.
[0093] Table 1 Performance data of silicon carbide ceramics
[0094] According to the table above and Figures 1-8 It is understood that the present invention mixes silicon carbide with rare earth metal elements and uses two-stage discharge plasma sintering to prepare silicon carbide ceramic materials with uniform microstructure, high density and excellent thermal conductivity.
[0095] according to Figures 1-3 As can be seen, in Example 2, during the first sintering stage, rare earth metal element Y, due to its strong reducing properties, undergoes a reduction reaction with SiO2 on the surface of silicon carbide powder, resulting in the in-situ generation of an oxygen-free transition phase Y3Si2C2 in the sintering intermediate. The main phase of this sintering intermediate is SiC, and the second phase consists of Y3Si2C2 and Y2O3, with a high content of the generated Y3Si2C2 phase. During the second sintering stage, this liquid environment not only effectively promotes the densification process of SiC ceramics but also optimizes the grain boundary structure, reduces phonon scattering sources, and continuously reduces the lattice oxygen and surface oxygen content of the material. This results in the final silicon carbide ceramic possessing a uniform phase distribution and a low-defect microstructure, thereby significantly improving thermal conductivity.
[0096] according to Figure 4 , 5 It is known that when rare earth metal element Sm is used as a sintering aid, no oxygen-free transition phase is generated in the sintering intermediate, but the resulting silicon carbide ceramic still has a uniform phase distribution and high thermal conductivity.
[0097] contrast Figures 6-8It can be seen that the amount of rare earth metal elemental Y powder added in Comparative Example 5 was relatively small. Although the oxygen-free transition phase (Y3Si2C2 phase) could still be synthesized in situ in the sintering intermediate, its proportion was reduced. Therefore, the amount of liquid phase generated during sintering was severely insufficient, leading to a decrease in density. At the same time, without the pinning constraint of the liquid phase, the resistance to grain boundary migration was greatly reduced, causing uncontrolled abnormal grain growth, forming a coarse and unevenly distributed microstructure with rough grain surfaces and black pores. This structure with insufficient density and coarse grains not only provides more space for the retention of oxygen impurities, but more importantly, the rapidly migrating grain boundaries directly cross over oxygen atoms that have not yet fully diffused out, resulting in a large amount of oxygen impurities being trapped inside the SiC lattice, and the lattice oxygen content is significantly increased. Lattice oxygen is a strong phonon point defect scattering source, which greatly reduces the mean free path of phonons and thus reduces thermal conductivity.
[0098] Compared to Example 2, Comparative Example 1 used a single sintering process, holding at 2050℃ for 2 hours. Under this high-temperature environment, the Y-containing liquid phase decomposed, rare earth metal Y volatilized and was lost, leading to increased microstructural defects, coarsening of pores, and a decrease in the thermal conductivity of the silicon carbide ceramic. Comparative Example 2 held at 1450℃ for 2 hours, followed by a further increase to 2050℃ and holding for 1 hour. Due to the prolonged holding at low temperatures, Y volatilization was significant, and the SiC grains became excessively coarsened in the liquid phase environment. This resulted in the presence of closed pores and microcracks within the blank, also affecting thermal conductivity. In Comparative Example 3, the second-stage sintering temperature rise rate was 5℃, equivalent to hot-pressing sintering. Rare earth metal Y was prone to slow oxidation or reaction with the graphite mold, introducing additional impurities. Furthermore, the extended sintering time in this stage easily caused liquid phase volatilization and loss, affecting the deoxidation and densification process. Liquid phase loss and higher lattice oxygen content led to a decrease in thermal conductivity. If the heating rate of the first-stage sintering is also reduced to 5°C, it further leads to Y volatilization, resulting in insufficient liquid phase to complete the ceramic densification process during the high-temperature sintering stage. In Comparative Example 4, no pressure is applied during the second-stage sintering, which is equivalent to pressureless sintering. Without external pressure assistance, capillary forces alone are insufficient to eliminate internal pores, leading to a decrease in density. At the same time, the slow heating rate results in slow oxidation and liquid phase loss, reducing thermal conductivity. If no pressure is applied during either stage of sintering, the density and thermal conductivity of the silicon carbide ceramic will further decrease. In Comparative Example 6, the addition of a large amount of rare earth metal elemental Y powder will generate a large amount of low thermal conductivity Y-containing grain boundary phase, while also exacerbating Y volatilization, generating pores and lattice defects. Multiple factors combined lead to a decrease in the material's thermal conductivity. In Comparative Example 7, the sintering temperature of the second-stage sintering is relatively low, resulting in an increase in grain boundary defects in the silicon carbide ceramic and an increase in lattice oxygen content, leading to a deterioration in thermal conductivity. In Comparative Example 8, Y3Si2C2 was added as a raw material without undergoing an in-situ reaction process. This resulted in uneven distribution of the grain boundary phase, poor interfacial bonding with the SiC matrix, and difficulty in effectively removing the SiO2 oxide layer from the powder surface. Consequently, the ceramic exhibited low density, high porosity, increased grain boundary defects, and decreased thermal conductivity. In Comparative Example 11, Y3Si2C2-coated SiC powder was first prepared using a molten salt method, followed by sintering at 2050℃. The Y3Si2C2 generated prematurely during the low-temperature molten salt stage was prone to agglomeration and coarsening, making it difficult to form a uniformly wetted liquid phase during high-temperature sintering, thus weakening the densification effect. Simultaneously, the coarsened grain boundary phase became a strong phonon scattering source, ultimately reducing both the ceramic's density and thermal conductivity.
[0099] In summary, by selecting rare earth metals as sintering aids and combining them with two-stage spark plasma sintering, this invention effectively reduces the lattice oxygen content of silicon carbide ceramics, optimizes the microstructure, and significantly improves thermal conductivity, showing significant application prospects in semiconductor heat dissipation components, high-temperature heat exchangers, and high-performance structural ceramics.
[0100] All aspects, embodiments, and features of this invention should be considered illustrative in all respects and not limiting of the invention; the scope of the invention is defined only by the claims. Other embodiments, modifications, and uses will become apparent to those skilled in the art without departing from the spirit and scope of the invention as claimed.
[0101] In the preparation method of this invention, the order of the steps is not limited to the listed order. For those skilled in the art, variations in the order of the steps without creative effort are also within the scope of protection of this invention. Furthermore, two or more steps or actions can be performed simultaneously.
[0102] Finally, it should be noted that the specific embodiments described herein are merely illustrative examples of the invention and are not intended to limit the implementation of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them; it is neither necessary nor possible to exemplify all embodiments here. However, these obvious variations or modifications derived from the essential spirit of the invention still fall within the scope of protection of the invention, and interpreting them as any additional limitation would contradict the spirit of the invention.
Claims
1. A method for preparing silicon carbide ceramics based on rare earth metals, characterized in that, Includes the following steps: (1) Silicon carbide powder with a molar ratio of 88:12 to 92:8 is mixed with rare earth metal element powder to obtain mixed powder; wherein, the rare earth metal element RE is selected from at least one of Yb, Sm, Gd, Y, Er and Dy; (2) Under an inert atmosphere, the mixed powder is placed in a spark plasma sintering furnace, a pressure of 1~100MPa is applied, and the temperature is raised to 1100~1540℃ at a heating rate of 20~60℃ / min for the first stage of sintering and held for 20~90min. Then, the temperature is continuously raised to 2010~2100℃ at a heating rate of 10~40℃ / min for the second stage of sintering and held for 20~90min to obtain silicon carbide ceramic.
2. The method for preparing silicon carbide ceramics based on rare earth metals according to claim 1, characterized in that, In step (1), the rare earth metal element RE is Y.
3. The method for preparing silicon carbide ceramics based on rare earth metals according to claim 1, characterized in that, In step (2), the pressure of the first stage of sintering is 10~40MPa.
4. The method for preparing silicon carbide ceramics based on rare earth metals according to claim 1, characterized in that, In step (2), the heating rate of the first stage sintering is 45~55℃ / min, the sintering temperature is 1410~1490℃, and the sintering time is 30~80min.
5. The method for preparing silicon carbide ceramics based on rare earth metals according to claim 1, characterized in that, In step (2), a liquid phase is formed after the first stage of sintering.
6. The method for preparing silicon carbide ceramics based on rare earth metals according to claim 1, characterized in that, In step (2), the pressure of the second stage sintering is 10~40MPa.
7. The method for preparing silicon carbide ceramics based on rare earth metals according to claim 1, characterized in that, In step (2), the heating rate of the second stage sintering is 22~30℃ / min, the sintering temperature is 2020~2070℃, and the sintering time is 30~80min.
8. A silicon carbide ceramic based on rare earth metals, characterized in that, It is prepared by the method for preparing silicon carbide ceramics based on rare earth metal elements as described in any one of claims 1 to 7.
9. The silicon carbide ceramic based on rare earth metals according to claim 8, characterized in that, The lattice oxygen content of the silicon carbide ceramic is ≤0.3wt%.
10. The silicon carbide ceramic based on rare earth metals according to claim 8, characterized in that, The thermal conductivity of the silicon carbide ceramic is >222 W / mK.